2022
DOI: 10.3390/antiox11081491
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Disease (Water Bubble Disease) of the Giant Freshwater Prawn Macrobrachium rosenbergii Caused by Citrobacter freundii: Antibiotic Treatment and Effects on the Antioxidant Enzyme Activity and Immune Responses

Abstract: The giant freshwater prawn, Macrobrachium rosenbergii, is an important and economical aquaculture species widely farmed in tropical and subtropical areas of the world. A new disease, “water bubble disease (WBD)”, has emerged and resulted in a large loss of M. rosenbergii cultured in China. A water bubble with a diameter of about 7 mm under the carapace represents the main clinical sign of diseased prawns. In the present study, Citrobacter freundii was isolated and identified from the water bubble. The optimum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 112 publications
0
10
0
Order By: Relevance
“…freundii is a common aquaculture pathogen that is able to infect aquatic animals and lead to high mortality. , For example, C. freundii could cause water bubble disease in Macrobrachium rosenbergii and bring some infectious diseases in Acipenser sinensis and carp fish. , Besides, the transfer assay of pWWTP-01 was also performed under surface water conditions (Text S1). Although the transfer frequency was lower than the laboratory condition after 16 h, the frequency could still reach 10 –6 after 48 h, which suggested that plasmid pWWTP-01 carried by DRB could also transfer in the surface water condition (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…freundii is a common aquaculture pathogen that is able to infect aquatic animals and lead to high mortality. , For example, C. freundii could cause water bubble disease in Macrobrachium rosenbergii and bring some infectious diseases in Acipenser sinensis and carp fish. , Besides, the transfer assay of pWWTP-01 was also performed under surface water conditions (Text S1). Although the transfer frequency was lower than the laboratory condition after 16 h, the frequency could still reach 10 –6 after 48 h, which suggested that plasmid pWWTP-01 carried by DRB could also transfer in the surface water condition (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…protein, which destroys and eliminates foreign bodies invading the body by hydrolyzing bacterial peptidoglycan, and takes the defense function of the body (Zhao et al, 2022). SOD is a crucial component of antioxidant enzymes, as an active oxygen scavenger, which can scavenge free radicals in the body and enhance the phagocytosis of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…91 Despite this, a 2022 study found C. freundii to be associated with juvenile mortalities of up to 30% in grow-out ponds in China, with laboratory challenges with C. freundii replicating clinical signs of disease seen in culture settings. 108 Typically, prawns infected with C. freundii develop a 7mm diameter bubble under the carapace, show loss of appetite, weight loss and inactivity. Clinical signs of disease are quickly followed by mortality and spread of the disease to other prawns.…”
Section: Notementioning
confidence: 99%
“…115 Citrobacter C. freundii 108 Juveniles (GO, L) "Water bubble disease (WDB)-Formation of a "water bubble" with a diameter of c. 7 mm under the carapace, loss of appetite, inactivity, weight loss. 108 Not described.…”
Section: Histopathological Signs Of Infectionmentioning
confidence: 99%
See 1 more Smart Citation